Kewirausahaan dan Motivasi Kewirausahaan terhadap Minat Menjadi Pengusaha Muda - Rahma Wulan Suci Nasution; Zuhrinal M. Nawawi (Economic Reviews Journal, 2022)
Entrepreneurship itself is a system or process of creating something that can be of monetary or additional value in the economy. In entrepreneurship, one thing that needs to be strengthened is that interest is encouraged by positive motivations from those closest to you. And interest is a movement of the heart and mind to make an object as a target because the object attracts sympathy and creates a feeling of pleasure towards the object. While motivation is a condition that can change or encourage and direct the desires and interests of individuals to carry out entrepreneurial activities. Likewise with young entrepreneurs, young entrepreneurs will be successful if they are surrounded by people who provide motivation and encouragement that are constructive. And the example I take here is how to build the spirit of young people in developing a business selling various takjil during the fasting month starting from kolding, coconut ice, fried foods and so on. Keywords : Entrepreneurship, Motivation, Interest, Young entrepreneurs